Exploring Relationship between Pakistani Teachers’ Pedagogical Beliefs and ICT Use for Teaching and Learning - Shameer, Ali Prasla (fi=Turun yliopisto|en=University of Turku|, 2016)
Background: The aim of present study is to investigate relationship between Pakistani teachers’ pedagogical beliefs and ICT use for teaching and learning. Previous studies found close relationship between pedagogical beliefs and teaching practices including use of ICT. However, variation in results is also reported and attributed to cultural and contextual differences. Methodology: Quantitative approach was used to study a sample of 231 Pakistani basic education teachers from middle and upper-middle range private schools, mostly from large urban centres. Results: This study confirmed previously study results that constructivist-compatible pedagogical beliefs are significantly related to both traditional and constructivist use of ICT. However, it is also found that traditional-transmission pedagogical beliefs are significantly related to traditional use of ICT – a finding not reported in previous studies. Some amounts of ICT training for pedagogical purpose exhibit significant impact on ICT use, in particular constructivist use of ICT. Similarly age also play a role as younger teachers are more likely to use ICT, however, no significant difference of pedagogical beliefs and ICT use was found between male and female teachers. Recommendation for practice and further investigation are made in chapter 5.